Extent of Awareness of Science Intermediate Stage Teachers in Saudi Arabia of the Skills of Twenty-First Century - Al Shaikh, Asma; Nawafleh, Mohammad Khair (Dirasat: Educational Sciences, 2021)
This study aims to identify the level of awareness of science teachers at the intermediate stage in the Kingdom of Saudi Arabia of the skills of the twenty-first century. The study sample consisted of (93) randomly chosen male (n= 48) and female (n= 45) teachers. To achieve the objectives of the study, the researchers used a descriptive survey method. The study tool was a questionnaire that consisted of (57) skills distributed over eight domains. The results of the study showed that the level of science teachers’ awareness of the skills of the twenty-first century was high, and that there was a statistically significant difference in the level of science teachers’ awareness of the skills of the twenty-first century due to gender in favor of females. There was no statistically significant difference in the level of science teachers’ awareness of the skills of the twenty-first century. The study recommends including science curricula and programs for preparing science teachers for the skills of the twenty-first century and conducting similar studies on science teachers at various academic levels.